HEAD AND NECK SOFT TISSUE SARCOMAS: DIAGNOSIS AND MANAGEMENT REVIEW - Michał Bereza; Mateusz Dembiński; Julia Prabucka-Marciniak; Edyta Szymańska (International Journal of Innovative Technologies in Social Science, 2025)
Soft tissue sarcomas (STS) of the head and neck are rare and histologically diverse malignancies that present unique diagnostic and therapeutic challenges due to their proximity to critical anatomical structures. They originate from various tissues, including fat, muscle, nerves, blood vessels, and others. Although they account for a small proportion of all STS, their management requires individualized care within experienced sarcoma centres. While surgery and radiotherapy remain the primary modalities, newer systemic and targeted strategies are increasingly being incorporated into clinical practice.  In this review we summarise current state of knowledge related to the diagnosis, staging, and treatment of head and neck STS in adults. We also discuss evolving systemic and targeted therapies with potential relevance to clinical oncology practice.